CIÊNCIA-TECNOLOGIA-SOCIEDADE EM DISCURSOS DA ESTRUTURA CURRICULAR EM DUAS LICENCIATURAS EM FÍSICA. - OLIVEIRA, Esteves Fernandes de (2021)
The constant transformations of a society driven by science and technology and, consequently, the need for the future education professional to deal with these questions motivated the reflections of this study, guided by the question: how does the Physics Degree course at the Universidade Federal do Amazonas (UFAM) and at the Universidade Federal do Maranhão (UFMA) have mobilized to insert discussions on the Science - Technology - Society relation, in the initial teacher education process? In an attempt to find clues to this question, the research objective was to analyze the curricular structure of the Physics Degree course at UFAM and UFMA, to see where and how discussions on science and technology and their relations with society are present in the initial teacher education. We based the analysis on assumptions of Science- Technology-Society, and principles of French Discourse Analysis, expressed in texts by Eni Orlandi, developed in Brazil. Disciplines in the curriculum of the courses and responses from professors of these institutions, given for interviews and a questionnaire, formed the research corpus. With the analysis, it was possible to infer that the Physics Degree course at UFAM, although without a specific discipline to deal with the theme, has a curricular structure that allows dealing with the subject, since the syllabus of some disciplines focuses on teacher training, committed to social transformation. At the conception of two professors, the course still needs to advance to conceive efficient formation on the subject. At UFMA, the Physics Degree course also does not present a specific discipline on the theme, but, we noticed subjects in the curriculum that can be considered starting points for reflections on Science, Technology, and Society (STS) since their syllabus deal with themes such as 'new technologies and pedagogical mediation' and 'the development of Sciences’, conducive to the practice of education through the STS approach. In the view of interviewed professors, the teaching staff formed by a majority of bachelors, and an old PPPC makes it hard to include discussions on the topic in the initial teacher education.